Book review: Strengthening Postgraduate Supervision. McKenna, S., Clarence-Fincham, J., Boughey, C., Wels, H. and van den Heuvel, H. eds. 2017. - Paxton, Moragh (Critical Studies in Teaching and Learning, 2023)
Strengthening  Postgraduate  Supervision is a  collection  edited by Sioux McKenna, Jenny  Clarence-Fincham, Chrissie Boughey, Harry Wels and Henk van den Heuvel. It emerged from the Strengthening  Postgraduate Supervision  (SPGS) Course which ran  45 times in 20  higher education institutions in South Africa. As the authors point out in the, preface, the book does not set out to provide a best practice guide to supervision but, rather, to present supervision as a complex and changing  pedagogy which is fostered through experience and critical reflection.